(untitled) (Research, Society and Development, 2025)
Sleep bruxism is a repetitive activity of the jaw muscles during sleep and is differentiated as rhythmic or non-rhythmic. The objective of the present study was to conduct a narrative review of the literature on the main forms of treatment for sleep bruxism in childhood. A search was carried out in the Virtual Health Library, PubMed and Scielo databases, between the years 2018 to 2024, and using the keywords “Sleep bruxism”, “Therapeutics”, “Children” and “Pediatric Dentistry”, all crossed in the search systems using the Boolean operators AND, OR or NOT. From the initial search, filters were applied, through the analysis of Title, Abstract and Full Text, obtaining in the end 18 articles, based on the previously established inclusion and exclusion criteria. The studies analyzed demonstrate the various types of treatments that can be considered, from intraoral devices, psychological treatment, pharmacological and homeopathic treatments, conduct according to the case, considering all treatments and their response over time in improving the child’s quality of life, in an individualized manner for each case and their response over time in improving the child’s quality of life.